2016
DOI: 10.1038/srep38727
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 1-catalyzed histone citrullination is essential for early embryo development

Abstract: Peptidylarginine deiminase (PADI) enzymes are increasingly being associated with the regulation of chromatin structure and gene activity via histone citrullination. As one of the PADI family members, PADI1 has been mainly reported to be expressed in the epidermis and uterus, where the protein in keratinocytes is thought to promote differentiation by citrullinating filament proteins. However, the roles of PADI1 in preimplantation development have not been addressed. Using a PADI1-specific inhibitor and Padi1-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…PADIs catalyzed histone citrullination also controls transcription regulation and chromatin organization [47][48][49][50][51][52][53][54][55][56]. Remarkably, citrullinated histones found to account for approximately 10% of all histone molecules, emphasizing the essential role of this posttranslational modification in many physiological processes in the nucleus [48].…”
Section: Impact Of Padi Family On Histone Citrullinationmentioning
confidence: 99%
See 1 more Smart Citation
“…PADIs catalyzed histone citrullination also controls transcription regulation and chromatin organization [47][48][49][50][51][52][53][54][55][56]. Remarkably, citrullinated histones found to account for approximately 10% of all histone molecules, emphasizing the essential role of this posttranslational modification in many physiological processes in the nucleus [48].…”
Section: Impact Of Padi Family On Histone Citrullinationmentioning
confidence: 99%
“…For example, during preimplantation and early-stage embryo development histone citrullination can lead to chromatin changes [49]. Specifically, PADI1 citrullinates both the histone H3 at 2, 8 and 17 positions (H3Cit2, 8, 17) and histone H4 at arginine 3 (H4Cit3) during 2-and 4-cell stage embryo development, which facilitates early embryo genome transactivation [50]. However, the potential implications of PADI1-directed histone citrullination had not been investigated yet.…”
Section: Impact Of Padi Family On Histone Citrullinationmentioning
confidence: 99%
“…[78] On the other hand, dimethylated H3R2 is reported to be a site for demethylation by Jumonji domain containing 6 protein (JMJD6), and H3R2 is a potential site for deimination by peptidylarginine deiminase 1 (PADI1) to produce citrulline. [79] Hence, while we have highlighted major crosstalk events between arginine methylation and other histone PTMs, there is a larger picture to appreciate.…”
Section: Interplay Of Arginine Methylation With Other Ptm Marks On Himentioning
confidence: 99%
“…1 G), indicating that Padi2 is likely the PAD that mediates citrullination activity at 2 dpf. Although previous studies have indicated that mammalian PAD1 and PADI6 are necessary for normal development (Esposito et al, 2007; Kan et al, 2012; Zhang et al, 2016), we found that the Padi2-deficient zebrafish did not display any gross morphological defects and had normal viability (Fig. S2, A and B).…”
Section: Resultsmentioning
confidence: 56%